Pengaruh Motivasi Kerja dan Kompensasi Kerja Terhadap Kinerja Karyawan Dengan Pandemi Covid-19 Sebagai Variabel Moderating pada Kantor Camat X Koto - Syuja Sobri Al Anshari; Elfiswandi; Ramdani Bayu Putra; Hasmaynelis Fitri (Yayasan Kawanad, 2022)
This study aims to assess how much, the effect of work motivation and work compensation on employee performance with the covid-19 pandemic as a moderating variable. The method of collection was done by distributing questionnaires, with a sample of 50 respondents in the population of the X Koto Sub-District Office, Tanah Datar. The analytical method used is Moderated Regression Analysis (MRA) using SPSS 26 data processing tool. The results show that (1) There is a positive and significant influence on Work Motivation on Employee Performance at the X Koto Sub-District Office, Tanah Datar. (2) There is a positive and significant effect of Work Compensation on Employee Performance at the X Koto Sub-District Office, Tanah Datar. (3) The Covid-19 pandemic can weaken the influence of Work Motivation on Employee Performance at the X Koto Tanah Datar Sub-District Office. (4) The covid-19 pandemic can weaken the influence between Work Compensation on Employee Performance at the X Koto Tanah Datar Sub-District Office. The contribution of work motivation and work compensation variables to employee performance is 0.525 or 52.5% while the remaining 0.475 or 47.5% is influenced by other variables.